Modelling farmer decision-making: the case of the Dutch pork sector. Issue 10 (5th October 2015) - Stefano Pascucci, Dr Liesbeth Dries, Professor Konstantinos Karantininis and Professor Gaetano Martino, Dr; Ambrosius, Floor H. W.; Hofstede, Gert Jan; Bock, Bettina B.; Bokkers, Eddie A.M.; Beulens, Adrie J.M.
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to develop a framework that models farmers' strategic decision making, taking into account that farmers adapt to institutional changes, given the social structure in which they are embedded. Design/methodology/approach – First, a theoretical framework was developed using the reasoned action approach, innovation diffusion research, identity research, and the theory of structuration. Second, the framework was refined based on insights gained through semi-structured interviews with seven pork farmers and six pork farming experts on innovation decisions in general and added-value market adoption in particular. Findings – The farmer decision-making framework distinguishes personal characteristics, social influence related to reference groups, and the institutional context that determines the space for manoeuvre. The interviews reveal the importance of context specific factors, such as trust in policy and market requirements, and point at general mechanisms of path dependency as a result of previous decision making and social influence related to identity reference groups. Originality/value – The authors include feedback mechanisms between on the one hand social structure and institutional context, and on the other, farmer decision making. The framework is designed to explore the combined influence of factors of decision making on sector behaviour and study the relation between individual and collective behaviour.